Reproductive characteristics of Keudawah (Rasbora arundinata (Lumbantobing, 2014)): Insights into a native species of Krueng Lanca River, Nagan Raya District, Aceh Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Abdan M, Sulistiono, Kamal MM, Mashar A, Butet NA. 2025. Reproductive characteristics of Keudawah (Rasbora arundinata, Lumbantobing 2014): Insights into a native species of Krueng Lanca River, Nagan Raya District, Aceh Province, Indonesia. Biodiversitas 26: 1451-1463. Keudawah (Rasbora arundinata (Lumbantobing, 2014)) is a freshwater fish native to Indonesia, particularly found in the waters of Nagan Raya. Understanding its reproductive biology is crucial for developing sustainable management and conservation strategies. Given this importance, this study aimed to assess the spawning season, sex ratio, Gonadal Maturity Stage (GMS), size at first gonadal maturity (LM50), and fecundity of R. arundinata in the Krueng Lanca River, Aceh Province, Indonesia. Sampling was conducted from January to December 2023 at six stations selected based on habitat characteristics and local fishermen’s recommendations. Fish were caught using gill nets with mesh sizes of 0.5 and 1.0 inches, as well as throw nets with a 6-meter diameter and a 0.5-inch mesh size during monthly sampling. The collected specimens were measured for total length and weighed, after which their gonads were analyzed to determine maturity stage, Gonadosomatic Index (GSI), and fecundity. The size at first gonadal maturity (LM50) was estimated using the Spearman-Karber method. A total of 2,225 specimens were collected, comprising 1,162 males and 1,063 females, with size distributions ranging from 34 to 121 mm (males) and 46 to 135 mm (females). The length-weight relationship is expressed as W = 8.17E-05L2.55 (R² = 0.88), while in females, it follows the equation W = 8.17E-05L2.11 (R² = 0.89). The results indicated that the sex ratio was slightly male-biased, averaging 1.09:1 (M:F). The LM50 was estimated at 86.98 mm for males, with a Gonadosomatic Index (GSI) of 6.96%-9.10%, and 94.77 mm for females, with a GSI of 10.30%-12.61%. Fecundity of R. arundinata ranged from 1,156 to 2,090 oocytes. The findings suggest that R. arundinata exhibits year-round reproductive activity, with peak spawning occurring in April and September. These insights are valuable for conservation planning and provide a foundation for future aquaculture development.
Keywords: Conservation management, fecundity, Keudawah, Rasbora arundinata, reproductive biology, spawning season